Comunidades de hongos actinomicetos en tres tipos de vegetación de la Amazonia colombiana: abundancia, morfotipos y el gen 16s ADNr - Inés Cardona, Gladys (2009)
Among soil microorganisms, Actinomycetes play an important role in the sustainability of natural and agricultural systems: decomposition of organic matter; deg-radation of recalcitrant compounds like lignin; nitrogen fixation; degradation of agricultural chemicals and biological control in plants and animals. We evaluated their diversity in soils under three different vegetation covers (pasture, tropical primary forest and stubble) at two depths in the Southern Colombian Amazon border. We collected five replicates per vegetation type (in each, three samples at 0-20cm and three at 20-30cm; for a total of 30 samples). Abundance and phenotypic diversity were determined by plate counting. Genomic DNA was extracted from the isolates: the 16s rDNA gene was amplified with specific primers, and its genetic diversity was estimated by means of an amplified restriction analysis (ARDRA). Actynomicetes abundance varied with vegetation and depth, possibly reflecting presence of earthworms, macro-fauna and physico-chemical character-istics associated to fertility, as well as organic matter, total bases, and optimal capacity to cationic interchange. Primary forests had the highest diversity. Sixteen morpho-types (six genera) were identified; Streptomyces was the most abundant everywhere. The heterogeneity of ARDRA patterns prevented species identification because of the intra-species variability in sequences of 16s rDNA operons. This community is a biological indicator of landscape alteration and could include new bio-active compounds of pharmaceutical interest.